COLLABORATIVE GOVERNANCE DALAM UPAYA PENURUNAN ANGKA STUNTING - Fardianti, Pimpi; Bintari, Antik (Universitas Djuanda, 2024)
This research is motivated by the high stunting rate in Tasikmalaya Regency in 2022. To reduce the stunting rate, the Tasikmalaya District Government collaborates with pentahelix elements. Therefore, it is important to identify the collaboration process to see the truth of the collaboration. The purpose of the research is to describe the collaboration process to reduce stunting in Tasikmalaya Regency through the dimensions of face-to-face dialogue, trust building, commitment to the process, shared understanding, and intermediate outcomes. This study uses a qualitative method of descriptive presentation. Data collection techniques through observation, interviews, and documentation. The technique of determining informants is done by purposive technique with a total of 9 informants. The theory used is the theory of collaborative governance according to Ansell and Gash by using five dimensions of the collaboration process as an analysis knife, namely face-to-face dialogue, trust building, commitment to process, shared understanding, and intermediate outcome. The results of the study prove that there is ineffectiveness in the collaboration process such as, communication between the elements involved is not optimal, trust and commitment between the elements involved have not been built equally, there is no shared understanding of the issue of reducing stunting rates, and the stunting rate in Tasikmalaya Regency has not decreased significantly. Based on the five dimensions of the collaborative governance process according to Ansell and Gash, it can be concluded that the things emphasized in the collaboration process have not been fulfilled, this is due to the inconsistency of policies regarding the involvement of collaborative elements, which affects the dimensions of collaborative governance according to Ansell and Gash. In addition, the programs issued by the Tasikmalaya Regency Regional Government in an effort to reduce the stunting rate are not sustainable so that they have not been able to reduce the stunting rate significantly.